“Third platform” and new requirements to education - Нестеров, Вячеслав Михайлович; Михайлова, Елена Георгиевна (Computer Tools in Education, 2015)
In the paper we consider current trends in IT education. The current state and the actual problems of IT industry are discussed. We examine the recent changes in curricula of IT-related courses as well as new tendencies in education technologies. Some causes of strengthening the connection between education and industry are discussed.
Keywords: information infrastructures; third platform; IT education